Gambaran Faktor-Faktor Risiko Postpartum Blues di Wilayah Kerja Puskesmas Blora - Krisdiana Wijayanti; Feri Anita Wijayanti; Erni Nuryanti (JURNAL KEBIDANAN, 2013)
Morbidity associated with psychological problems is a major health problem experienced in postpartum period, as a risk factor for the development of serious mood disorders. Postpartum blues is a phenomenon that is difficult to detect because people regard as psychological disorders are maternal instincts. This study aims to determine the incidence of postpartum blues on postpartum mothers and their characteristics in Blora Public Health Centre. This study was a descriptive survey with cross-sectional approach. The population were mothers after 2 – 10 days of childbirth in September 2013 in Blora Public Health Centre with 70 respondents. Samples were taken by saturated sampling. The instrument was questionnaire. The results showed that 48.6% experienced on the baby blues. The risk factors were age (20-35 years 84.3%), parity (multiparous 61.43%), family inco-me (Rp500,000-Rp1.000.000,00 64.3%), job (jobless 62.9%), education (higher education 53%), family support (strongly support 91.4%), delivery type (vaginal delivery 58%), premenstrual syndrome history 58.6%, breast-feeding 100%. Based on this research, the researchers suggest midwives provide the psychological needs of mothers after childbirth and provide information about the physiological changes in postpartum period to prevent postpartum blues.